2020
DOI: 10.1029/2019ms002014
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Atlantic Meridional Overturning Circulation to Model Resolution in CMIP6 HighResMIP Simulations and Implications for Future Changes

Abstract: A multimodel, multiresolution ensemble using Coupled Model Intercomparison Project Phase 6 (CMIP6) High Resolution Model Intercomparison Project (HighResMIP) coupled experiments is used to assess the performance of key aspects of the North Atlantic circulation. The Atlantic Meridional Overturning Circulation (AMOC), and related heat transport, tends to become stronger as ocean model resolution is enhanced, better agreeing with observations at 26.5°N. However, for most models the circulation remains too shallow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
76
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 104 publications
18
76
3
Order By: Relevance
“…This suggests that the highly intermittent Agulhas leakage is not properly captured by the low‐resolution simulation and the interocean exchange is through a rather laminar flow, which could reduce its impacts on OHC variability on interannual time scales. The findings of this work might be of particular importance for the adequate choice of model resolution in studies that are strongly linked to OHC variability and its influence on climate and they are in agreement with a recent study by Roberts et al (2020) who demonstrated that a high model resolution might be essential to represent MHT according to observations. It demonstrates the need for the application of high‐resolution climate models when investigating processes such as rainfall pattern variability and monsoon modifications or predictions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that the highly intermittent Agulhas leakage is not properly captured by the low‐resolution simulation and the interocean exchange is through a rather laminar flow, which could reduce its impacts on OHC variability on interannual time scales. The findings of this work might be of particular importance for the adequate choice of model resolution in studies that are strongly linked to OHC variability and its influence on climate and they are in agreement with a recent study by Roberts et al (2020) who demonstrated that a high model resolution might be essential to represent MHT according to observations. It demonstrates the need for the application of high‐resolution climate models when investigating processes such as rainfall pattern variability and monsoon modifications or predictions.…”
Section: Discussionsupporting
confidence: 92%
“…resolution in studies that are strongly linked to OHC variability and its influence on climate and they are in agreement with a recent study by Roberts et al (2020) who demonstrated that a high model resolution might be essential to represent MHT according to observations. It demonstrates the need for the application of high-resolution climate models when investigating processes such as rainfall pattern variability and monsoon modifications or predictions.…”
Section: 1029/2020gl089908supporting
confidence: 91%
“…In CMIP6 HighResMIP and OMIP simulations (see Fig. 1a, b), the AMOC transport more often than not becomes stronger at higher ocean resolution [20], and in coupled models, this tends to be driven by enhanced convection in the Labrador Sea [73,75]. For both CMIP5 models [76] and CMIP6 HighResMIP [73], there tend to be too deep mixed layers in the Labrador Sea in order for the AMOC strength to be comparable with observations (noting that this is particularly true in NEMO models, suggesting that the model structure as well as resolution may be a factor).…”
Section: Atlantic Meridional Overturning Circulationmentioning
confidence: 96%
“…For both CMIP5 models [76] and CMIP6 HighResMIP [73], there tend to be too deep mixed layers in the Labrador Sea in order for the AMOC strength to be comparable with observations (noting that this is particularly true in NEMO models, suggesting that the model structure as well as resolution may be a factor). When projecting future climate, this convection tends to reduce more quickly than that in the Nordic Seas [73], which means that the higher-resolution models have a stronger AMOC decline in the future. The effect of convection changes in the Nordic Seas is linked to the AMOC via the overflows.…”
Section: Atlantic Meridional Overturning Circulationmentioning
confidence: 99%
See 1 more Smart Citation